Auctions Versus Posted-Price Selling - Ruqu Wang (Queen's University, Department of Economics, 1991)
wo most popular selling methods – posted-price selling and auctions – are compared in this paper. We confirm the common belief that auctions are most often used when the distribution of the object's value is widely dispersed. The choice of selling methods usually depends on the costs of displaying, storing and auctioning. In the absence of auctioning costs, auctioning at every instant is optimal. The 'dispersion' of a distribution is then formally defined and developed. Using the definition of dispersion, we prove that auctions becomes preferable when a potential buyer's valuation becomes more dispersed. Finally, the optimization of a social planner is studied and we find that the monopoly seller's price can be higher or lower than that of the social optimum.
Keywords: 330